2011
DOI: 10.3390/ijms12085238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Fertilization on Synthesis of Primary and Secondary Metabolites in Three Varieties of Kacip Fatimah (Labisia Pumila Blume)

Abstract: A split plot 3 by 4 experiment was designed to examine the impact of 15-week variable levels of nitrogen fertilization (0, 90, 180 and 270 kg N/ha) on the characteristics of total flavonoids (TF), total phenolics (TP), total non structurable carbohydrate (TNC), net assimilation rate, leaf chlorophyll content, carbon to nitrogen ratio (C/N), phenyl alanine lyase activity (PAL) and protein content, and their relationships, in three varieties of Labisia pumila Blume (alata, pumila and lanceolata). The treatment e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
81
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 53 publications
18
81
5
Order By: Relevance
“…Beyond this, N also has other functions in plant life, such as those related with biomass yield (Rodrigues, Afonso, Ferreira, & Arrobas, 2016); presently, it was confirmed that high rates of N increase both the number and size of leaf cells (Yadav et al, 2011). Regarding bioactive constituents, and despite the existence of conflicting results, it has been shown that N availability not only influences the secondary metabolites production in a predictable manner, but also plant growth and differentiation processes (Aires et al, 2006;Ibrahim, Jaafar, Rahmat, & Rahman, 2011). Thus, it becomes increasingly evident that different N rates influence the biosynthesis of active constituents by cultivated medicinal plants (Karimi, Jaafar, & Ahmad, 2013;Tavarini, Sgherri, Ranieri, & Angelini, 2015).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Beyond this, N also has other functions in plant life, such as those related with biomass yield (Rodrigues, Afonso, Ferreira, & Arrobas, 2016); presently, it was confirmed that high rates of N increase both the number and size of leaf cells (Yadav et al, 2011). Regarding bioactive constituents, and despite the existence of conflicting results, it has been shown that N availability not only influences the secondary metabolites production in a predictable manner, but also plant growth and differentiation processes (Aires et al, 2006;Ibrahim, Jaafar, Rahmat, & Rahman, 2011). Thus, it becomes increasingly evident that different N rates influence the biosynthesis of active constituents by cultivated medicinal plants (Karimi, Jaafar, & Ahmad, 2013;Tavarini, Sgherri, Ranieri, & Angelini, 2015).…”
Section: Introductionmentioning
confidence: 89%
“…A similar scenario was also observed in Labisia pumila (Benth. & Hook) indicating that the manipulation of N fertilization levels may be an effective method to improve the expression of secondary metabolites (Ibrahim et al, 2011). However, in general, research is overlooking the fact that the availability of N might be a determinant/important factor on secondary metabolism in medicinal and aromatic plants.…”
Section: Introductionmentioning
confidence: 99%
“…In general, when there is addition of N in the soil there is no decrease in secondary metabolites. Ibrahim et al (2011) found a reduction of flavonoids, anthocyanins and ascorbic acid by increasing the N doses on "kacip fatimah" (Labisia pumila, Primulaceae) as well as a lower antioxidant power of its extracts, which may be related to a lower incidence of light in plants due to the increased vegetative growth caused by N.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there is no clarity about its effect on the allelopathic activity and on the concentration of allelochemicals. Some authors mention the increase of secondary metabolites under low N availability in the soil (Ibrahim et al, 2011), while others indicate that N increases the concentration of phenolic acids (Chou and Lee, 1988;Ma et al, 2015). Phenolic compounds may, in turn, be in a higher or a lower concentration, depending on the physiological age of the plants.…”
Section: Introductionmentioning
confidence: 99%
“…In chrysanthemum (Chrysanthemum morifolium), Liu et al (2010) observed a reduction in antioxidant activity with increased N supply and attributed this reduction to the competition for Lphenylalanine, a precursor of both proteins and polyphenols, since these compounds inhibit the oxidizing action. For Labisiapumila (a medicinal herb from southeastern Asia), the activity of phenylalanine ammonia lyase was reduced with increasing doses of N, and it was observed that this behavior was accompanied by a reduction in the content of flavonoids and phenolic compounds (Ibrahim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%